Kesejahteraan Psikologis Pada Remaja Pengajar TPA Kadus IV Desa Sindon - Pramesti Regita Sari; Annisa Dian Kharisma (Pusat Riset dan Inovasi Nasional, 2024)
Psychological well-being is something that is important in realizing the tasks of adolescent development. This research uses a qualitative method carried out with a phenomenological approach. Phenomenological research is a type of qualitative research that looks and hears more closely and in detail an individual's explanation and understanding of their experiences. The subjects in this study were 7 people. The results of this research show that the level of psychological well-being of TPQ teachers who are still teenagers is still relatively high. Furthermore, the aspects of self-acceptance, positive relationships with others, self-acceptance, positive relationships with others, mastery of the environment, life goals and personal growth are also at a high level.